Contributions to shrimp taxonomy — Editorial - de Grave, Sammy; Fransen, Charles H.j.m. (Zootaxa, 2010)
The idea of devoting a special issue of Zootaxa to shrimp taxonomy was born during a late night meeting between the two editors in Leiden in November 2008. We discussed inviting all currently active shrimp taxonomists to come together in a single volume, dedicated to the description of new taxa in this fascinating group of animals. To be honest, our plan was not entirely altruistic, as at the time we were entering the final phase of compiling a species level list of all described taxa within the shrimp-like Decapoda (Dendrobranchiata, Stenopodidea and Caridea). As was done prior to publication of the crab list (Ng et al. 2008), we liked the idea of compiling a volume to bring to light as many descriptions as possible, both in order for the catalogue, once completed, to remain current for perhaps a few more months (in this fast paced field), but also to offer our colleagues a chance to publish upon (and sort out) some of the nomenclatorial problems any branch of descriptive taxonomy faces.